2008
DOI: 10.1111/j.1469-8137.2008.02555.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a rice transgene flow model for predicting maximum distances of gene flow in southern China

Abstract: Summary• We aimed to establish a rice gene flow model based on (i) the Gaussian plume model, (ii) data from a three-location × 3-yr field experiment on transgene flow to common rice cultivars (Oryza sativa), male sterile (ms) lines (O. sativa) and common wild rice (Oryza rufipogon), and (iii) 32-yr historical meteorological data collected from 38 meteorological stations in southern China during the rice flowering period.• The concept of the gene flow coefficient (GFC) is proposed; that is, the ratio of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…The concerns regarding the environmental impact of GE plants include those worries related to their possible invasiveness in ecosystems (Snow et al 2005); outcrossing and horizontal gene transfer (Yao et al 2008, Rong et al 2010); development of resistant pest populations that would again require the input of pesticides (Tabashnik et al 2009); and effects on nontarget organisms (NTOs). In the case of IRGE plants, effects on NTOs is a particular concern, as these organisms provide important ecosystem services such as biological control (predators and parasitoids), pollination, and decomposition (Kennedy 2008, Romeis et al 2008a.…”
mentioning
confidence: 99%
“…The concerns regarding the environmental impact of GE plants include those worries related to their possible invasiveness in ecosystems (Snow et al 2005); outcrossing and horizontal gene transfer (Yao et al 2008, Rong et al 2010); development of resistant pest populations that would again require the input of pesticides (Tabashnik et al 2009); and effects on nontarget organisms (NTOs). In the case of IRGE plants, effects on NTOs is a particular concern, as these organisms provide important ecosystem services such as biological control (predators and parasitoids), pollination, and decomposition (Kennedy 2008, Romeis et al 2008a.…”
mentioning
confidence: 99%
“…Previous studies found that GM rice may hybridize with traditional cultivars (Messeguer et al 2001(Messeguer et al , 2004Rong et al 2005Rong et al , 2007Jia et al 2007;Yuan et al 2007;Yao et al 2008), weedy rice (Zhang et al 2003(Zhang et al , 2006Chen et al 2004;Messeguer et al 2004;Sanchez Olguin et al 2009), and wild rice (Chen et al 2004;Yao et al 2008). A few GM rice lines have been developed in Korea, including those tolerant to herbicides (Lee et al 2007) and abiotic stresses (Jang et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, PMGF frequencies estimated from a limited number of field experiments may not represent PMGF frequencies of a particular plant species under diverse environmental conditions. As a comparison, mathematical modelling can provide relatively quick estimation of PMGF frequencies for different plant species under diverse environmental conditions (Yao et al 2008; Rong et al 2010; Hu et al 2014). Undoubtedly, mathematical modelling provides a powerful complement of the field-experiment-based method to estimate PMGF frequencies, provided that the model can accurately simulate PMGF (Rong et al 2010; Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%